2021
DOI: 10.13189/ujer.2021.090710
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Utilization of TikTok to Improve Oral English Communication Competence among EFL Undergraduate Students

Abstract: The field of English language communication competence learning and acquisition has been revolutionized by the increasing development of technology. The application of social media has now been popular inside and outside of the English language classrooms. The development of technology in the past fifty years, the more recent mobile devices and the Web 2.0 technology have provided numerous opportunities for its use in improving English communication competence. TikTok, one of the popular social media platforms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 45 publications
(68 reference statements)
2
29
0
Order By: Relevance
“…According to Xiuwen & Razali (2021), expressed that TikTok can be considered as an assessment language tool. Teachers can use TikTok to assess students' learning outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Xiuwen & Razali (2021), expressed that TikTok can be considered as an assessment language tool. Teachers can use TikTok to assess students' learning outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…So, both parties could bene t mutually [2]. As the largest group of international students [4] international Chinese EFL students' overseas studies should be emphasized to improve the quality of international education services [5]. However, Zhai and Razali [6] reported that international Chinese EFL students face obstacles in English language communication.…”
Section: Introductionmentioning
confidence: 99%
“…For international students to better their academic achievement, they need to master the basic English communication competence and make adequate preparations before studying abroad [6]. erefore, English communication education for international students studying in Malaysian higher education institutions should be prioritized [5].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a decline in English communication skills among primary school children has emerged due to this situation. Referring to this issue at hand, the researchers of this paper were stipulated to revamp their teaching methods to adapt to the current pandemic restriction utilizing the most accessible piece of technology on top of being extremely popular among youngsters, social media specifically TikTok mobile application (Xiuwen & Razali, 2021). TikTok has recently paved its way through the education world as a very effective yet entertaining language learning tool in this technology-driven era and surprisingly remained significantly valid in times of pandemic (Xiuwen & Razali, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Referring to this issue at hand, the researchers of this paper were stipulated to revamp their teaching methods to adapt to the current pandemic restriction utilizing the most accessible piece of technology on top of being extremely popular among youngsters, social media specifically TikTok mobile application (Xiuwen & Razali, 2021). TikTok has recently paved its way through the education world as a very effective yet entertaining language learning tool in this technology-driven era and surprisingly remained significantly valid in times of pandemic (Xiuwen & Razali, 2021). Through the TikTok platform, knowledge is no longer exclusive content tailored to any specific group of people but is now made affordable, convenient and flexible through instantaneous and reliable worldwide sharing.…”
Section: Introductionmentioning
confidence: 99%